The Life Cycle of the Parasitic Crustacean, Lernanthropus latis Yamaguti, 1954 (Copepoda: Lernanthropidae), on Marine-Cultured Fish, Lates calcarifer, from Setiu Wetland, Terengganu - Nur Qamarina Abdul Khalid; Faizah Shaharoum-Harrison (Journal of Parasitology Research)
Parasitic crustaceans of Lernanthropus latis were isolated from the host, the seabass, Lates calcarifer, obtained from a cage culture in Setiu Wetland, Terengganu. The adult females with egg were kept alive in vials containing 20 mL of filtered seawater and incubated at 30°C. The eggs were monitored every hour and the hatching periods were recorded. Three developmental stages were observed, namely, nauplii I, nauplii II, and infective copepodid. The infective copepodids were then transferred into a tank containing 60 litres of seawater with 150 fingerlings for infection purpose. One fish was sacrificed every 24 hr to inspect the next developmental stage. As a result, six more stages were obtained within 298 hrs starting from the infection day. The stages were known as fixed copepodid I, fixed copepodid II, fixed copepodid III, fixed copepodid IV, preadult, and adult. Parasitic L. latis takes a 483 hr period to complete a life cycle.